1988
DOI: 10.1111/j.1600-051x.1988.tb01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, microbiological and immunological features of subjects with destructive periodontal diseases

Abstract: 76 subjects with prior evidence of destructive periodontal diseases were monitored clinically and immunologically every 2 months for up to 5 years. Clinical parameters measured included bleeding on probing, gingival redness, plaque accumulation, suppuration, pocket depth and attachment level. Blood samples were taken by venipuncture and serum antibody levels to a series of 18 subgingival species determined. 33 of these subjects showed evidence of active disease during the monitoring period, based on changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(71 citation statements)
references
References 17 publications
4
66
0
1
Order By: Relevance
“…The pathogen Porphyromonas gingivalis has been associated with active disease in both systems. [1][2][3][4][5][6] In periodontal disease, an epithelial barrier separates the microbial biofilm from host tissues, whereas in periapical periodontitis; there is direct tissue invasion and parenteral contact of bacteria with the host immune system. Remarkably, actual microbial invasion of bone rarely occurs in periapical periodontitis, suggesting that the local immune response contains the infection but at the same time mediates bone resorption.…”
mentioning
confidence: 99%
“…The pathogen Porphyromonas gingivalis has been associated with active disease in both systems. [1][2][3][4][5][6] In periodontal disease, an epithelial barrier separates the microbial biofilm from host tissues, whereas in periapical periodontitis; there is direct tissue invasion and parenteral contact of bacteria with the host immune system. Remarkably, actual microbial invasion of bone rarely occurs in periapical periodontitis, suggesting that the local immune response contains the infection but at the same time mediates bone resorption.…”
mentioning
confidence: 99%
“…P. gingivalis is more frequently isolated, and is present in elevated levels, in subgingival pockets from patients with periodontitis compared to gingivitis or periodontally healthy subjects. Its numbers are further increased at sites of active tissue destruction and are reduced in successfully treated sites but commonly remain high in sites with disease recurrence (6,15,43). Implantation of P. gingivalis leads to periodontal disease initiation in monkeys (16) and in mice (4,35).…”
mentioning
confidence: 99%
“…Studies have shown that P. intermedia is associated with periodontal breakdown in type I diabetics (40) and is frequently encountered in periodontal lesions or abscesses associated with destructive disease (5,7,9,10,25,33,35,36,39). Thus, these studies provide strong clinical support for a role for P. intermedia in the development of periodontal diseases.…”
mentioning
confidence: 99%